United Nations Office on Drugs and Crime : UNODC - Vereinte Nationen - Office on Drugs and Crime (2016)
[Dt.:] Büro der Vereinten Nationen für Drogen, Verbrechensbekämpfung und Drogenmissbrauch. - [Engl.:] Office of the United Nations for Drugs and crime prevention and the prevention of drug abuse